Knowledge about pregnancy prevention in Mexican adolescents - Rodríguez-Vázquez, Nancy; Moreno-Monsiváis, María Guadalupe; Gómez-Melasio, Dafne Astrid; Gómez-Rodríguez, Gustavo Alfredo; Apodaca-Armenta, Rosario Eduardo (Horizonte Sanitario, 2022)
Objective: Establish the relationship between knowledge of pregnancy prevention, age of sexual debut, number of contraceptive methods ever used and personal characteristics of the adolescent such as sex, age and schooling.Materials and methods: A descriptive, cross-sectional, correlational, cross-sectional study, 2509 Mexican adolescents aged 14 to 19 years participated. The items measuring knowledge in the dimensions of sexual health, reproductive health and condom use of the psychometric scale of knowledge, attitudes and practices in sexual and reproductive health were used.Results: The mean knowledge of pregnancy prevention was 17.21 (SD = 4.72) from 0-27. Knowledge is significantly related to adolescent age (r = 0.325; p = 0.01), to the number of contraceptive methods used (r = 0.210; p = 0.01) and an incipient relationship with age at sexual debut (r = 0.074; p = 0.01). Knowledge is slightly higher in females (M = 17.42; SD = 4.58) relative to males (M = 16.92; SD = 4.89), as well as in college adolescents (M = 18.71; SD = 4.19). Adolescents using 3 or more contraceptive methods showed greater knowledge (M = 19.46; SD = 4.11).Conclusions: Knowledge about pregnancy prevention increases with age, age at sexual debut and schooling. The findings are important to develop information strategies on contraceptive methods and sexual and reproductive health, in an accessible and egalitarian way for women and men from an early age and in basic schooling, with the intention that the adolescent is responsible from the beginning of sexual life to prevent and postpone pregnancy through knowledge as a fundamental tool.